The European Central Bank at Ten - Haan, Jakob; Berger, Helge; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Coming at a critical juncture for the euro, the book takes stock of the ECB's experience during its first ten years and discusses the way ahead. The articles are written by well-known experts in the field and provide the reader with a comprehensive overview of relevant policy issues, including the ECB$1 (Bs communication and its monetary strategy and instruments.s
Inflation Differentials in the Euro Area: A Survey -- The ECB$1 (Bs Monetary Analysis Revisited -- Euro Area Monetary Policy in Uncharted Waters -- The Communication Policy of the European Central Bank: An Overview of the First Decade -- Governance and Monetary Policy Decision-Making at the ECB -- The ECB, Financial Supervision, and Financial Stability Management.s
Keywords: Economics; Europe -- Economic policy; Macroeconomics; Economics/Management Science; Macroeconomics/Monetary Economics; European Integration; Political Science, general